Reducing the Loss of <12 µm Copper to Tailings - A. Ang-Ug; L. Gurieff (Society for Mining, Metallurgy & Exploration, 2018)
"The Phu Kham Cu-Au mine in Laos is owned and operated by Phu Bia Mining Limited. The deposit is a complex and low grade Cu-Au porphyry ore. The rougher feed has a particle size distribution of 80% passing 110 µm, and the rougher concentrate is reground for cleaning to 80% passing 25 µm. The Cu losses in the cleaning circuit are primarily in the <12 µm fraction. A randomised paired ON-OFF test of magnetic conditioning in one of the two parallel cleaner 1 circuits was undertaken. The results showed that with magnetic conditioning there was approximately a 10% reduction in the <12 µm Cu distribution in the cleaner 1 tail to a 98% level of confidence. The Cu distribution in the <12µm fraction is a less variable measure of changes in the <12µm Cu recovery, therefore, this was used to evaluate the impact of magnetic conditioning. Subsequently, magnetic conditioning was installed in both cleaner 1 circuits and the plant results monitored after this installation. Comparing the plant results immediately before and after this installation showed that there was a 20% reduction in <12µm Cu losses to the cleaner tail. INTRODUCTION The Cu-Au, Phu Kham Mine (PKM) is located within PanAust's Phu Bia Mining Contract Area in Laos, approximately 140 kilometres from the capital city, Vientiane. PKM is PanAust's flagship operation and the significant cash flow generated by PKM has supported PanAust’s growth, while contributing to a strong balance sheet. PKM comprises an open-pit mine and a conventional milling and flotation operation that produces and exports a Cu and precious metals concentrate. The concentrate contains around 23% Cu, 6 ppm Au and up to 35 ppm silver. Process Overview The PKM deposit consists of complex heterogeneous mineralogy horizons of Cu-Au stockwork and skarn mineralisation. It contains areas of soft-leached zones, overlying transition zones and supergene chalcocite dominant secondary Cu mineralisation and clay-rich gangue. Areas of high As and Zn also pose a challenge in treating the highly variable ore. In addition, hardness of the ore increases with deposit depth. The ROM is hauled to a primary gyratory crusher to produce a coarse ore stockpile with size distribution suitable for the 13 MW semi-autogenous mill. The SAG product feeds two parallel ball mills each equipped with a cyclone cluster producing a product particle size distribution of 80% passing 110 µm. The conventional flotation circuit consists of two parallel rougher banks. The rougher concentrates feed the regrind cyclone where the underflow is split and reports to two parallel, 3MW, M10000 IsaMills. The regrind mill discharge combines with the regrind cyclone overflow with a product particle size distribution 80% passing 25 µm and reports to the Jameson cell."